2006
DOI: 10.1007/s11270-006-9174-2
|View full text |Cite
|
Sign up to set email alerts
|

Oil residuals in lowland forest soil after pollution with crude oil

Abstract: Research on oil residuals in lowland forest soil was carried out in 6 sample plots in the lowland forest ecosystem located in an oil field. Four plots were differently affected in terms of discharged oil and the time lapsed after the accident, as well as in terms of micro-relief terrain features. One plot was established in a reclaimed mud ditch site, while the control plot was set up in a micro-relief elevation outside the influence of oil pollution.Total petroleum hydrocarbon (TPH) concentrations were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…More reduction was encountered at a 15% level of oil as compared to a 10% level of oil. Plants growing in oil-contaminated soil are documented to have a reduction in growth due to the accumulative impact of toxicity of hydrocarbons and inadequate aeration because of blockage of soil pores with crude oil ( Pernar et al, 2006 ). Soil with a high level of oil has led to an increase in growth inhibition because of difficulty in the water and ion absorption.…”
Section: Discussionmentioning
confidence: 99%
“…More reduction was encountered at a 15% level of oil as compared to a 10% level of oil. Plants growing in oil-contaminated soil are documented to have a reduction in growth due to the accumulative impact of toxicity of hydrocarbons and inadequate aeration because of blockage of soil pores with crude oil ( Pernar et al, 2006 ). Soil with a high level of oil has led to an increase in growth inhibition because of difficulty in the water and ion absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Petroleum hydrocarbons (PHCs) usually consist of alkanes (linear or branched), cycloalkanes, aromatic hydrocarbons or more complex chemicals (Pernar et al, 2006). There are three main approaches in dealing with contaminated sites: identification of the problem, assessment of the nature and degree of the hazard, and the best choice of remedial action.…”
Section: Remediation Of Hydrocarbons and Heavy Metals Contaminated Somentioning
confidence: 99%
“…The 47 kobo profit difference could be attributed to effects of crude oil exploitation activities in crude oil producing communities. These effects resulted principally from oil spillage that reduced the fertility of most arable lands and gas flaring which reduced yield of food crops in the area (Odu, 1983;Ukaegbu and Okeke, 1987;Olemeforo, 2000;Ezedike, 2000;Pernar et al, 2006).…”
Section: Costs and Returns Of Ybcm Enterprisementioning
confidence: 99%
“…Okoli (2006) reported that pollution due oil exploitation is caused by gas flaring, pipeline leakage, oil water dump and oil spills. They have deleterious consequences on the agro-ecosystem that in turn adversely affects food crops productivity (Ukaegbu and Okeke, 1987;Olemeforo, 1994;2000;Ezedike, 2000;Pernar et al, 2006;Alam et al, 2010). Besides, Opukri and Ibaba (2008) also observed that oil related environmental problems such as oil spillages, gas flaring, among others, have diminished the productivity of oil producing communities.…”
Section: Introductionmentioning
confidence: 99%